Equatorial Guinea’s Cabinet Dataset (1994-2020) - Sá, Ana Lúcia; Sanches, E. (Harvard Dataverse, 2021)
We introduce a dataset on Equatorial Guinea’s cabinet composition between 1994, after the reintroduction of multipartyism, and 2020. The dataset contains information on the names of cabinet members, portfolios, position in the cabinet, number of times a politician has been appointed to cabinet, party membership, ethnicity, and family ties with the President Teodoro Obiang Nguema Mbasogo.